2014
DOI: 10.1523/jneurosci.5188-13.2014
|View full text |Cite
|
Sign up to set email alerts
|

Frequency-Dependent, Cell Type-Divergent Signaling in the Hippocamposeptal Projection

Abstract: Hippocampal oscillations are critical for information processing, and are strongly influenced by inputs from the medial septum. Hippocamposeptal neurons provide direct inhibitory feedback from the hippocampus onto septal cells, and are therefore likely to also play an important role in the circuit; these neurons fire at either low or high frequency, reflecting hippocampal network activity during theta oscillations or ripple events, respectively. Here, we optogenetically target the long-range GABAergic projecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 56 publications
2
36
0
Order By: Relevance
“…In agreement with this, current-clamp recordings of SACs showed a small but significant depolarization in 5HT (2.4 Ϯ 0.3 mV; n ϭ 7, P Ͻ 0.01; not shown). We estimated the reversal potential for the 5HT current to be Ϫ26.2 Ϯ 5.9 mV (Mattis et al 2014, see MATERIALS AND METHODS). Thus it is consistent with a mixed cation conductance and has a greater driving force at more negative resting membrane potentials.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In agreement with this, current-clamp recordings of SACs showed a small but significant depolarization in 5HT (2.4 Ϯ 0.3 mV; n ϭ 7, P Ͻ 0.01; not shown). We estimated the reversal potential for the 5HT current to be Ϫ26.2 Ϯ 5.9 mV (Mattis et al 2014, see MATERIALS AND METHODS). Thus it is consistent with a mixed cation conductance and has a greater driving force at more negative resting membrane potentials.…”
Section: Resultsmentioning
confidence: 99%
“…The reversal potential of the 5HT response in SACs and MCs was estimated using the brief voltage steps to measure input resistance. From measurements of the 5HT-evoked current at Ϫ60 and at Ϫ65 mV, we created a simple, two-step current-voltage curve assuming the simple addition of linear membrane conductances (Mattis et al 2014).…”
Section: Methodsmentioning
confidence: 99%
“…1a). Some commonly used promoter fragments that confer cell type preference and are applicable in lentivirus or adeno-associated virus (AAV) vectors are linked to the following markers 73 : calcium/calmodulin-dependent protein kinase type II subunit-α (CaMKIIα; biased towards excitatory cells in cortical regions 3,4 ), hypocretin 74 , oxytocin 75 , D2 dopamine receptor 41 , glial fibrillary acidic protein (GFAP; for astrocytes), myelin basic protein (MBP; for oligodendrocytes) and somatostatin 76 . This method has illuminated how hypocretin-producing lateral hypothalamic neurons regulate sleep–wake transitions 74 and how nucleus accumbens (NAc) D2 dopamine receptor-expressing cells modulate risk taking 41 .…”
Section: Cell Type-specific Opsin Expressionmentioning
confidence: 99%
“…Our previous work has shown that gain modulation in cholinergic MS‐DB neurons is possible with hyperpolarization (Melonakos, White, & Fernandez, ). Further, hippocamposeptal (somatostatin + GABAergic) neurons most effectively evoke hyperpolarization in cholinergic MS‐DB neurons when driven at 50 Hz (Mattis et al, ). Since optogenetic activation of cholinergic MS‐DB neurons blocks ripples in the hippocampus, while increasing theta power and coherence (Vandecasteele et al, ), it would be interesting to see if 50 Hz somatostatin + GABAergic neuron firing could reduce gain in cholinergic neurons, reducing their output and increasing the incidence of ripples.…”
Section: Discussionmentioning
confidence: 99%